Three-dimensional porous carbon materials and their composites as electrodes for electrochemical energy storage systems. (18th September 2019) - Deng, Xiaoyang; Li, Jiajun; Ma, Liying; Sha, Junwei; Zhao, Naiqin
Abstract : This review describes the recent progress of 3D porous carbon materials and their composites as electrodes for electrochemical energy storage systems. Abstract : Electrode materials play a vital role in electrochemical energy storage devices and many efforts have been devoted to exploring optimized high-performance electrode materials. 3D porous carbon materials and their composites have attracted significant attentionas advanced electrode materials. In this review, we first summarize the current design and synthesis of 3D porous carbon materials with various structures. Furthermore, the recent progress in electrochemical energy storage applications of 3D carbon materials and their composites is discussed, including supercapacitors, lithium-ion batteries, sodium-ion batteries, lithium–sulfur batteries, and hybrid energy storage devices. In addition, we discuss our perspectives on future challenges followed by the research opportunities in 3D porous carbon materials.